Tomato methionine sulfoxide reductase B2 functions in drought tolerance by promoting ROS scavenging and chlorophyll accumulation through interaction with Catalase 2 and RBCS3B - Cui, Long (Plant science : an international journal of experimental plant biology, 2022)
Copyright © 2022 Elsevier B.V. All rights reserved.